Carla's Comfort Foods : Favorite Dishes from Around the World - Hall, Carla; Ko, Genevieve; Janisch, Frances (New York : Atria Books, 2014)
"Featuring 130 recipes with new variations on soulful favorites, this cookbook covers the culinary globe on an ingenious, delicious mission: to capture the international flavors of comfort.Comfort food is universal. It's also delicious, particularly when cooked up by The Chew co-host and Top Chef fan favorite Carla Hall. With a flair for classic American comfort food, especially from the South, Carla brings her quirky and fun-loving style to every recipe. In Cooking with Carla, you'll find a mouthwatering variety of foods from around the world. Each section covers a cooking technique or main ingredient and then follows with international variations. Stove-top chicken starts with Carla's classic recipe for Southern Chicken with Milk Gravy. Then you'll learn to make French Chicken in Dijon Cream as well as West African Spicy-Sweet Stew; following Southern Grits, there's Italian Polenta and Jamaican Breakfast Porridge; and next to Italian-American Lasagna, you'll find recipes for Irish Shepherd's Pie and Mexican Enchiladas. With a fun international spice chart that shows what seasonings belong to which cuisines, Cooking with Carla takes you on a culinary adventure, striking a unique balance between the heartfelt stories and flavors she's encountered around the world. "With this sweet tome in the home kitchen anyone can make thoughtful, tasty food with real style" (Mario Batali)"--
"Featuring 130 recipes with new variations on soulful favorites, this cookbook covers the globe to capture the international flavors of comfort"--
Includes index.
Keywords: International cooking; Comfort food; COOKING / Regional & Ethnic / American / Southern States; COOKING / General; COOKING / Regional & Ethnic / Soul Food; Cookbooks